ANALISIS PENGARUH ROE, ROA, EPS, DPS, DOL, DAN DFL TERHADAP MARKET VALUE ADDED PADA INDUSTRI MANUFAKTUR DI BEI TAHUN 2011-2014 - Sitorus, Michael; Demi Pangestuti, Irene Rini (Faculty of Economics and Business Diponegoro University, 2016)
This Research aimed to analyze the influence of Return on Equity, Return on Assets, Earnings Per Share, Dividend Per Share, Degree Of Operating Leverage and Degree Of Financial Leverage to Market Value Added. Case study on manufacture company in Indonesia Stock Exchange during the period 2011- 2014 Research population used manufacture company in Indonesia Stock Exchange during period 2011-2014. By using purposive sampling method obtained a sample of 19 companies. Company data used in this study was obtained from the Indonesian Capital Market Directory for 2010-2014 and www.idx.com. The analysis technique used is Ordinary Least Squares Regression (OLS). The results showed only a Dividend Per Share (DPS) which has positive and significant against Market Value Added, while ROE, ROA, EPS, DOL, and DFL does not affect the Market Value Added.